Prediction of CO2 gas permeability behavior of ionic liquid–polymer membranes (ILPM). Issue 17 (20th January 2017) - Mannan, H. A.; Mukhtar, H.; Murugesan, T.; Man, Z.; Bustam, M. A.; Shaharun, M. S.; Abu Bakar, M. Z.
ABSTRACT: Predicting the gas permeability of ionic liquid‐polymeric membranes (ILPM) is of great importance for the design of efficient gas separation membrane materials. The available models for the prediction of CO2 gas permeability through ionic liquid‐polymeric membranes were analyzed using the literature data. Maxwell model was selected for modification due to relatively accurate prediction capability. The Maxwell model was modified for ionic liquid‐polymeric membranes by incorporating model parameter k for the effectiveness of volume fraction of dispersed phase. The established methodology was tested for different ionic liquid‐polymeric membrane systems for validation. A satisfactory agreement was observed for predicted and experimental permeability by using the current approach. This method can be used for the prediction of CO2 gas permeability through ionic liquid‐polymeric membranes. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44761. Abstract :